Pengaruh Brand Image dan Kualitas Produk Terhadap Kepuasan Serta Dampaknya Pada Loyalitas - Darmawan, Rahmad Tirta; Tjahjaningsih, Endang (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine the Influence of Brand Image and Product Quality on Satisfaction and Its Impact on Loyalty. The sample in this study were consumers who had purchased and consumed Aqua mineral water. The sampling technique in this study used purposive sampling technique. The data collection technique was carried out using an offline questionnaire obtained by 100 respondents. There are 3 hypotheses tested in this study. Data analysis used in this study is respondent description analysis, variable description, validity test, reliability test, and multiple linear regression analysis. The results of the study indicate that brand image has a positive effect on customer satisfaction, product quality has a positive effect on customer satisfaction, consumer satisfaction has a positive effect on customer loyalty.